1998
DOI: 10.1093/oxfordjournals.schbul.a033317
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Consequences of the Gender Difference in Age at Onset of Schizophrenia

Abstract: The ABC (age, beginning, course) schizophrenia study was commenced in 1987 to generate and test hypotheses about pathogenic aspects of schizophrenia. One of the main branches of the study focused on how gender influences the age distribution of onset, symptomatology, illness behavior, and early course in schizophrenia. Proceeding from one of the rare, strikingly deviating, consistent findings--the gender difference in age at first admission--we launched a systematic search for explanations by generating and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
127
3
16

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(162 citation statements)
references
References 52 publications
16
127
3
16
Order By: Relevance
“…In many cases, particularly in males, first onset occurs already before the age of twenty (Häfner et al, 1998b), so that early detection should start in late adolescence. The expense and effort of pre-selections via self-reports are disproportionately lower to extensive screening procedures using clinical interviews.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, particularly in males, first onset occurs already before the age of twenty (Häfner et al, 1998b), so that early detection should start in late adolescence. The expense and effort of pre-selections via self-reports are disproportionately lower to extensive screening procedures using clinical interviews.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study (Talledo et al, 2009) found no direct relationship between PPI and estrogen levels in healthy women. Furthermore, within schizophrenia populations, a later age of illness onset, less severe forms of schizophrenia, superior response to antipsychotics, and better functional and social outcomes are reported for women than men with schizophrenia (Castle and Murray, 1991;Faraone et al, 1994;Castle et al, 1995), supposedly because of a neuroprotective role of estrogen in women (Häfner et al, 1998;Kulkarni, 2009). Female schizophrenia patients also show greater symptom severity during the periods of low estrogen (eg, postpartum) and lower symptom severity during the periods of high estrogen (eg, pregnancy, Riecher-Rössler et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, certain aspects of cocaine taking and addiction are more severe in women including prevalence of cocaine dependence in adolescence (Kandel et al, 1997), age and severity of use at intake (Robbins et al, 1999), and cocaine-induced craving (Kosten et al, 1993;Robbins et al, 1999). In contrast to stimulant addiction, women are somewhat protected from Parkinson's disease relative to men (Bower et al, 1999;Baldereschi et al, 2000), and the age of onset of schizophrenia is about 6 years later in women than men (Lindamer et al, 1997;Hafner et al, 1998;Leung and Chue, 2000). This set of clinical findings suggests that underlying sex differences in dopaminergic function exist in humans.…”
Section: Introductionmentioning
confidence: 99%